Problematika Pemerolehan Bahasa Amiyah Pada Mahasiswa Mesir (Analisis Psiko-sosiolinguistik) - Fahira, Putri Aldina Fahira; Setiyawan, Agung; Bastari, Muhammad Bagus; Alhanun, Zaenab Zannuba; Padilah, Yulva Maya (LP2M IAIN Sultan Amai Gorontalo, 2025)
Background: The 'Ammiyah language is a variation of Arabic used in informal communication and daily conversations in Egypt, in contrast to Standard Arabic, which is employed in formal and academic contexts. New students encounter various challenges when entering university life, making the adaptation process more difficult. Aims: This study aims to analyze the challenges faced by new Indonesian students in acquiring the 'Ammiyah language in Egypt. Methods: This research employs a case study method with a descriptive qualitative approach. Data were collected through in-depth interviews with ten new Indonesian students in Egypt. Results: The findings indicate that new students experience several difficulties in acquiring the 'Ammiyah language, including (1) dialectal differences between Egyptian 'Ammiyah and the previously learned Standard Arabic (Fushah), (2) difficulties in understanding informal vocabulary and expressions in 'Ammiyah, and (3) psychological barriers that hinder their adaptation to using 'Ammiyah in a new environment. Implications: The results of this study are expected to provide insights for educational institutions in designing more effective 'Ammiyah language learning programs for foreign students in Egypt, as well as assist students in overcoming challenges related to acquiring the 'Ammiyah language in a new environment.